2005
DOI: 10.1111/j.1365-2958.2005.04596.x
|View full text |Cite
|
Sign up to set email alerts
|

Silkworm pathogenic bacteria infection model for identification of novel virulence genes

Abstract: SummarySilkworms are killed by injection of pathogenic bacteria, such as Staphylococcus aureus and Streptococcus pyogenes , into the haemolymph. Gene disruption mutants of S. aureus whose open reading frames were previously uncharacterized and that are conserved among bacteria were examined for their virulence in silkworms. Of these 100 genes, three genes named cvfA , cvfB , and cvfC were required for full virulence of S. aureus in silkworms. Haemolysin production was decreased in these mutants. The cvfA and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
196
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 160 publications
(210 citation statements)
references
References 30 publications
(38 reference statements)
7
196
1
2
Order By: Relevance
“…Furthermore, a large number of silkworms can be produced at low cost. We demonstrated that antibiotics used clinically to treat infected humans are effective in silkworms, and that the ED 50 values of the antibiotics used in the silkworm infection model are consistent with those obtained in mammalian animal models (Hamamoto et al, 2004(Hamamoto et al, , 2005Hamamoto & Sekimizu, 2005;Kaito et al, 2002Kaito et al, , 2005. Silkworms have enzymes, P450s and conjugating enzymes (Hamamoto et al, 2005;Li et al, 2005;Luque et al, 2002) that are involved in metabolizing antibiotics.…”
Section: Introductionsupporting
confidence: 73%
“…Furthermore, a large number of silkworms can be produced at low cost. We demonstrated that antibiotics used clinically to treat infected humans are effective in silkworms, and that the ED 50 values of the antibiotics used in the silkworm infection model are consistent with those obtained in mammalian animal models (Hamamoto et al, 2004(Hamamoto et al, , 2005Hamamoto & Sekimizu, 2005;Kaito et al, 2002Kaito et al, , 2005. Silkworms have enzymes, P450s and conjugating enzymes (Hamamoto et al, 2005;Li et al, 2005;Luque et al, 2002) that are involved in metabolizing antibiotics.…”
Section: Introductionsupporting
confidence: 73%
“…2). RNase Y was shown to affect production of virulence factors either through expression of the accessory gene regulatory locus, agr or independently (Kaito et al, 2005;Nagata et al, 2008). Recently Marincola et al (2012) performed a transcriptomic analysis to decipher the effect of RNase Y on global gene regulation.…”
Section: Ribonucleases As Possible Co-factors Of Srnasmentioning
confidence: 99%
“…Ribonucleases (RNases) play a critical role in RNA metabolism and have been largely associated with the regulation of factors involved in bacterial pathogenicity [3,4]. In particular, the single-stranded specific endoribonuclease Y (RNase Y) is crucial for the virulence of Gram-positive pathogens such as Staphyloccocus aureus, Clostridium perfringens and Streptococcus pyogenes [59]. In S. aureus , RNase Y stabilizes the mRNA coding for the two-component system SaeRS, which acts as a general regulator of virulence [8,10].…”
Section: Introductionmentioning
confidence: 99%